Molecular Identification and Analysis on Differential Pathogenicity of Cylindrocarpon Species Associated With Ginseng Root Rust Rot in Northeastern China - Li, Zibo; Sun, Chunlei; Liu, Xinran; Zhou, Rujun (Frontiers in Plant Science, 2022)
Panax ginseng C. A. Meyer is one of the most important medicinal herbs in China. It is known for its high medicinal value and economic value. The ginseng root rust rot (RRR) has always been one of the important diseases troubling the ginseng industry. The yield reduction rate of RRR is ~30%. To understand why the Cylindrocarpon species bring about the ginseng RRR in Northeastern China, this study isolates 45 strains from samples collected in Liaoning, Jilin, and Heilongjiang provinces. The rDNA-internal transcribed spacer (ITS) sequence was analyzed to identify the pathogenic species. The morphological characteristics of colonies and conidia of each strain on potato dextrose agar (PDA) medium were observed, and the pathogenicity difference between different pathogenic species was analyzed by pricking method and determining the cell wall degrading enzyme activity. The BLAST alignment analysis shows that the homology of rDNA-ITS between 45 strains and Cylindrocarpon is more than 99%, among which 28 are identified as Cylindrocarpon destructans, three are identified as C. destructans var. destructans, and 14 are identified as Ilyonectria robusta. The colony diameters of all 45 isolated range from 4.21 ± 0.16a to 7.78 ± 0.25c cm after several days of incubation. Among all the species, I. robusta has the fastest growth rate, and C. destructans var. destructans has the slowest growth rate. Pathogenicity test results show that the pathogenicity of C. destructans var. destructans is the strongest, followed by C. destructans. I. robusta has relatively weak pathogenicity.